Breast Care Interventions to Enhance Breast Milk Production in Post-Caesarean Mothers: A Study at Ir. Soekarno Hospital, Sukoharjo - Damayanti, Diah Ayu; Diktina, Amalia Arifatul; Prastiwi, Yohana Ika; Mauritania, Ardhini (Jurnal Kegawatdaruratan Medis Indonesia, 2025)
Background: Cesarean section is a surgical procedure involving incisions in the abdomen and uterus to deliver a baby. Breastfeeding obstacles that occur in post-section cesarean mothers are caused by surgical pain that affects the mother's comfort and can inhibit the pituitary glandula nerves that produce the hormone oxytocin, which plays a role in the breastfeeding process. Breast care refers to interventions aimed at facilitating breast milk production. These interventions can be beneficial both prenatally and postnatally. Objective: This study aims to describe the impact of breast care on breast milk flow in mothers who have undergone cesarean section at Ir. Soekarno Hospital, Sukoharjo District. Method: A descriptive case study approach was employed, involving two respondents. Pre-test and post-test assessments were conducted using an observation sheet to evaluate breast milk flow based on 10 specific indicators. Results: Both respondents exhibited suboptimal breast milk flow before breast care interventions. Following the interventions, both respondents demonstrated significant improvements, achieving optimal breast milk flow. Conclusion: The findings indicate a notable enhancement in breast milk flow among the respondents after receiving breast care, suggesting the efficacy of such interventions in supporting lactation.